2019
DOI: 10.15210/rle.v22i4.16642
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Acquisition in English as a Foreign Language: Digital Gameplaying The Sims

Abstract: The use of digital technological resources for educational settings is a quite recent phenomenon (Savi; Ulbricht, 2008). Although recent research emphasizes the importance of integrating technology into the curriculum, its use can only be effective for learning if well integrated in a meaningful way in the classroom (Prensky, 2007; Squire, 2006). This article aims to characterize vocabulary acquisition and the use of the digital game The Sims, and to investigate if and how it can assist vocabulary of English a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…This approach includes four components : the first one is the somatic through which the teacher asked students to find out the taught vocabulary in or out of the class. This develop their vocabulary as it was proved in (Kelley,2010;Endayani;Liu, 2014 ;Lorenset,2009;Lorenset, and Tumolo, 2019. ) The second component of SAVI approach is the auditory through which the teacher were writing words on the board and pronouncing them for students or playing a CD on to give them the chance to listen to the right pronunciation of words and this improved the participants' listening skill as was proved in (Durmus and Gulec ,2015;Kurniawati, et al , 2013, Pancasilawan, 2013.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This approach includes four components : the first one is the somatic through which the teacher asked students to find out the taught vocabulary in or out of the class. This develop their vocabulary as it was proved in (Kelley,2010;Endayani;Liu, 2014 ;Lorenset,2009;Lorenset, and Tumolo, 2019. ) The second component of SAVI approach is the auditory through which the teacher were writing words on the board and pronouncing them for students or playing a CD on to give them the chance to listen to the right pronunciation of words and this improved the participants' listening skill as was proved in (Durmus and Gulec ,2015;Kurniawati, et al , 2013, Pancasilawan, 2013.…”
Section: Discussionsupporting
confidence: 56%
“…The results of Lorenset and Tumolo (2019) indicated that the Sims is effective for vocabulary acquisition in EFL as it uses common vocabulary and offers contextual learning as well as a new virtual life for players. Sok (2014,p.21) indicated that research in vocabulary acquisition has developed.…”
Section: Developing Vocabularymentioning
confidence: 99%
“…The findings displayed that the use of computer games as an instructional means can influence the way how computer games are used in the lectures, the characteristics of the game, in-class hardware and software infrastructure, and the perceptions and attitudes of teachers and pupils towards the computer games. Lorenset and Tumolo [32] revealed that games could enhance students' physical and mental capabilities, attract respondents' attention all the time, and put them in a competition with themselves and others to achieve specific goals.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The most positive ratio was found in secondary school studies. These studies also included the most games for entertainment such as L.A. Noire [79,155] and The Sims [102,156]. These games were aimed at vocabulary and had a high concentration of game elements but were implemented for different reasons.…”
Section: Are There Differences Between Bespoke and Off-the-shelf Games Regarding Their Impact On Observed Outcomes Within A Specific Age mentioning
confidence: 99%